PENGARUH PENERAPAN STRATEGI PEMECAHAN MASALAH DALAM PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA SMP NEGERI 15 PEKANBARU - Yulia Herma; Sehatta Saragih; Suhermi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is a pre-experimental research with the static group comparison study design, that aims to determine whether the ability of Mathematical Problem Solving of students of SMP Negeri 15 Pekanbaru which aplly problem solving strategy in cooperative learning NHT better than students of SMP Negeri 15 Pekanbaru which aplly cooperative learning NHT. This research involved experimental and control classes that consists of 33 students and 28 students. The test score of student’s mathematical problem solving ability is the data that used to test hypothesis of the research. Based on the test score, obtained the average value of mathematical problem solving ability of students in experimental class was 81 and the average value of mathematical problem solving ability of students in control class was 43. And from the Independent Sample Test, obtained tarithmetic > ttable (9,45 > 2,002). It is mean that H0 has rejected and H1 has accepted. The average value of test mathematical problem solving ability of students in experimental class is higher than the average value of test mathematical problem solving ability of students in control class.. It can be conclude that the ability of Mathematical Problem Solving of students of SMP Negeri 15 Pekanbaru which aplly problem solving strategy in cooperative learning NHT better than students of SMP Negeri 15 Pekanbaru which aplly cooperative learning NHT school year 2016/2017.Keywords: Problem Solving Strategy, Mathematical Problem Solving Ability, Pre-experimental Research